PENGARUH HARGA, PELAYANAN DAN KELENGKAPAN OBAT TERHADAP KEPUTUSAN PEMBELI APOTEK - Risa Mustika; Andini Setyo Anggraeni (LPPM-ITEBA, 2023)
The existence of pharmacies as health services and pharmaceuticals has an important role in the development of the current health sector, especially in the pandemic era. A good analysis of the pharmacy business is needed to find strategies that can be implemented to develop the business. One analysis that can be done is to analyze the factors that influence purchasing decisions. The factors to be analyzed are price, service and completeness. Data will be analyzed using multiple linear regression analysis. Based on the results of the analysis and discussion, it can be concluded that price has a negative effect on buyer decisions at Endar Farma Pharmacy with a drug price regression coefficient of 0.178; The service and completeness of the drug has a positive influence on the buyer's decision at Endar Farma Pharmacy, with a service regression coefficient value of 0.326 and a regression coefficient value of drug completeness of 0.401. The three variables above are very influential on the decision of Endar Farma Pharmacy buyers, this can be seen from the percentage obtained from these 3 variables of 54.3%.